#EMPODERAD@S: um estudo sobre construções identitárias de mulheres que discutem empoderamento feminino na internet - Gizelle de Souza Mageste (2018)
This thesis refers to the study carried out with five women who write about female empowerment on the internet with the objective of understanding, from the interviewees' point of view, the relationship between active participation in virtual communities on the internet and the construction processes identity and female empowerment. These women build, from their personal pages and publications, virtual communities that give them an extension in the possibilities of identity construction. The focus of the research was qualitative, using as research strategies methods that aim to give voice to the research subject. Data collection was performed in two stages. The first involved the integration of the researcher in the virtual communities to be studied and systematic observation of the relational dynamics of these communities. The second stage involved the selection of women who fit the chosen cut: women who produced content on women's empowerment in a public and frequent way, and who formed virtual communities around the topics discussed. The data analysis of the interviews was carried out through the thematic analysis of content, emphasizing the thematic routes constructed in the narratives and the characters presented in their narratives. The presentation and analysis of data were performed considering each narrative as a case. In each of them, the thematic paths presented in the narrative were analyzed and serve as context for the identifications and belongings claimed by the interviewees, as well as the main actions narrated in the interviews aiming at empowerment, both individually and collectively. The analysis of the thematic pathways has brought important elements for the investigation of the identity construction of women and their empowerment process. The main contributions of this research to organizational studies involve, first, theoretical-conceptual aspects such as the construction of a model that integrates the internet, identity and empowerment. And secondly, the mapping of emerging and current themes that require deeper research, such as digital entrepreneurship and empowerment, organizational practices in digital entrepreneurship, the use of the Internet by social movements and the intersection of class, race and gender in online empowerment processes.